Gut microbiome profiles may be related to atypical antipsychotic associated overweight in Asian children with psychiatric disorder: a preliminary study - Hao, Shao-rui; Zhou, Yuan-yue; Zhang, Xue; Jiang, Hai-yin (Frontiers in Cellular and Infection Microbiology, 2023)
Objective Atypical antipsychotics (APs) modify the gut microbiome, and weight gain in response to AP could be mediated by the gut microbiome. Thus, the present study aimed to explore the changes in the gut bacterial microbiome in AP-exposed children with obesity. Methods To rule out the confounder of AP indication, the gut bacterial microbiome was compared between healthy controls (Con) and AP-exposed individuals with overweight (APO) or normal weight (APN). Fifty-seven AP-treated outpatients (21 APO and 36 APN) and 25 Con were included in this cross-sectional microbiota study. Results AP users, regardless of body mass index, exhibited decreased microbial richness and diversity and a distinct metagenomic composition compared to the Con. Although no differences in the microbiota structure were observed between APO and APN groups, the APO group was characterised by a higher abundance of Megamonas and Lachnospira. Additionally, the differences in the microbial functions were observed between APO and APN groups. Conclusions The gut bacterial microbiota of APO children revealed taxonomic and functional differences compared to Con and APN. Further studies are needed to verify these findings and to explore the temporal and causal relationships between these variables.